Y generáció félelmei az önvezető autóktól = Y generation's fears from self-driving cars - Szikora, Péter; Madarász, Nikolett (Közép-Európai Közlemények, 2018)
The purpose of this study is to explore a quickly developing, therefore very exciting topic. The usage and production of self-driving cars has become a leading industry in almost every area of the world, so nowadays, self-driving cars are not just opportunities of the future, but are an important part of our present. In this study we give a short insight into the international literature of autonomous cars, starting with the evolution of them, describing the different steps and the six levels of autonomy. Several studies dealt with this issue and it turned out that people are more concerned than enthusiastic about the appearance of this new technology. Their fears are not unreasonable. Ethical dilemmas emerged and there is the risk of unauthorized persons entering the system. Thus, the main part of our research is to examine the fears of people and to detect the impact of self-driving cars on people.